Artisanal Skills, Watchmaking, and the Industrial Revolution: Prescot and Beyond. (7th December 2022) - Cummins, Neil; Gráda, Cormac Ó
Abstract : The role of skills and human capital during England's Industrial Revolution is the subject of an old but still ongoing debate. This paper contributes to the debate by assessing the artisanal skills of watchmakers and watch tool makers in southwest Lancashire in the eighteenth century and their links to apprenticeship. The flexibility of the training regime and its evolution are discussed, as is the decline of the industry.